2014
DOI: 10.3906/vet-1303-3
|View full text |Cite
|
Sign up to set email alerts
|

Growth traits and survival rates of Akkaraman lambs in breeder flocks in Konya Province

Abstract: Nanoscale ZrO 2 was synthesized on a multiwall carbon nanotube (MWCNT) and designed as a new solid phase extractor for metal ion preconcentration. The characterization of the synthesized material was achieved by transmission electron microscope (TEM) and X-ray diffraction (XRD). Then the new nanoscale material was applied to preconcentration of lead(II) from various matrices. Different experimental factors including pH of the sample solution, sample volume, flow rate of the sample solution, and volume and conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
6
6
1
Order By: Relevance
“…The average birth weight (BWT) were found as 4.13 kg varying between 3.91 and 4.33 in the present study. In a study conducted by Bingöl and Aktaş (Bingol 1998;Aktas et al 2014), type of birth and sex of lamb affected BWT significantly. In some other researches, it was reported that age of dam did not have significant effect on BWT (Vanli and Ozsoy 1986;Koncagul et al 2013).…”
Section: Resultsmentioning
confidence: 97%
“…The average birth weight (BWT) were found as 4.13 kg varying between 3.91 and 4.33 in the present study. In a study conducted by Bingöl and Aktaş (Bingol 1998;Aktas et al 2014), type of birth and sex of lamb affected BWT significantly. In some other researches, it was reported that age of dam did not have significant effect on BWT (Vanli and Ozsoy 1986;Koncagul et al 2013).…”
Section: Resultsmentioning
confidence: 97%
“…According to FAO data, Turkey ranks 7 th globally in terms of total sheep population with a stock of approximately 31 million [4] . Of the current sheep population of Turkey, 45% consists of a fat-tailed breed called the Akkaraman, which is bred in the central Anatolia [5] . The Akkaraman breed meets most of the mutton demand in Turkey in spite of low-quality pasture and poor climatic conditions, to which the breed has adapted well [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Growth curve models provide a set of parameters that describe growth pattern and estimate the expected weight of animals at certain ages. In addition, the parameters obtained from growth functions are highly heritable and have been used in selection studies (Ulutas et al, 2010;Daskiran et al, 2010;Koncagul et al, 2013;Sen et al, 2013;Aktas et al, 2014;Bahreini Behzadi et al, 2014;Kopuzlu et al, 2014;Ghavi Hossein-Zadeh, 2015). Farmers are interested in collecting knowledge of genotypic and phenotypic relationships among weights of lambs during all phases of growth.…”
Section: Introductionmentioning
confidence: 99%